Shit talk in shitty terrain: Flushing Indian feminism through YouTube's comedic conduits. Issue 2 (3rd April 2021) - Ghosh, Pragya; Parameswaran, Radhika; Rao, Pallavi
ABSTRACT: This article examines the ways in which YouTube's comedy-driven drama, Ladies Room, set in six women-only toilet sanctuaries across Mumbai, mines the semiotics of unruliness to push against the boundaries of upper-caste Indian feminine respectability. Drawing upon comedy studies and feminist theory, we deconstruct the two millennial protagonists Dingo & Khanna's transgressive behaviors, body politics, and charged conversations about the sexist and cutthroat environments of corporate and new media branding careers. In conclusion, while Ladies Room' s cultural politics disrupt the agendas of conservative Hindu nationalism and Bollywood's neoliberal feminism, we also point to the show's collusion with caste and class hierarchies.